Heterogeneous catalyst as well as preparation method and application thereof

By synthesizing metal/metal phosphide heterostructure catalysts with visible light-driven dye-sensitized photocatalytic system at room temperature, the problems of high energy consumption and polluted gases in the prior art are solved, and the efficient decomposition of sodium hypophosphite is achieved, and a cheap, simple and efficient catalytic system is provided.

CN119633861APending Publication Date: 2025-03-18SHANDONG AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411815954.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The method of preparing metal/metal phosphide heterostructure catalysts in the prior art has problems of high energy consumption and contaminated gases, making it difficult to achieve efficient catalytic decomposition of sodium hypophosphite to produce hydrogen, and the catalytic process usually requires photocatalytic or electrocatalytic conditions.

Method used

A metal/metal phosphide (M/MP) heterostructure catalyst is synthesized under normal temperature and pressure by using a visible light-driven dye-sensitized photocatalytic system, and the catalyst is directly decomposed at room temperature to produce hydrogen.

Benefits of technology

It realizes efficient catalytic decomposition of sodium hypophosphite at room temperature to produce hydrogen, avoids high-temperature calcination and the generation of polluted gas, and provides a cheap and simple catalytic system with good hydrogen production performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633861A_ABST
    Figure CN119633861A_ABST
Patent Text Reader

Abstract

The invention relates to the field of new materials and catalytic hydrogen production, in particular to a heterogeneous catalyst and a preparation method and application thereof.The specific preparation method comprises the steps that a metal source and a photosensitizer are added into a mixed solvent of triethylamine and deionized water, sodium hypophosphite monohydrate or sodium hypophosphite is added to serve as a phosphorus source, the mixture is mixed to be uniform, and the heterogeneous catalyst is prepared. Stirring under the illumination of visible light to obtain a heterostructure catalyst dispersed in the solution, and performing post-treatment on the heterostructure catalyst dispersed in the solution to obtain nanoparticles of the heterostructure catalyst; the preparation of the catalyst is driven by visible light, high-temperature calcination or heating treatment is not needed, hydrogen can be generated in situ in the preparation process, the reaction of decomposing sodium hypophosphite to generate hydrogen by the prepared catalyst does not need to be carried out under the photocatalysis or electrocatalysis condition, and hydrogen can be generated by standing at normal temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new materials and catalytic hydrogen production, and in particular to a heterogeneous catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen energy has the advantages of being clean, zero carbon, and having high calorific value, and is considered to be one of the new energy sources to solve the problem of energy demand. Compared with fossil energy, hydrogen energy does not produce pollution when used and is environmentally friendly. At the same time, hydrogen energy is used in many fields such as fuel cells, power generation, and transportation, and is also an important industrial raw material in the fields of petroleum, chemical industry, electronics, metallurgy, aerospace, etc. However, a stable, efficient, and safe hydrogen storage and release system is the key to the effective use of hydrogen energy. In recent years, chemical material hydrogen storage has the advantages of high hydrogen storage density, low hydrogen storage pressure, good safety, and high hydrogen release purity. The volume hydrogen storage density is also higher than that of liquid hydrogen storage, and its development prospects are very broad. At this stage, potential hydrogen storage materials mainly include carbon-based hydrogen storage materials, metal organic framework materials and covalent organic compound materials, metal hydrides (such as Mg2Ni, LaNi5, Ti-Fe, ZrMn), metal coordination hydrides (such as NaBH4), ammonia borane, etc. Although hydrogen storage materials are widely studied at this stage, their complex synthesis process, relatively expensive price, and certain dangers limit their application. Among potential hydrogen storage materials, sodium hypophosphite (NaH2PO2) has the advantages of being stable and rich in hydrogen. It is also non-toxic, cheap, and can be obtained in large quantities from the wet process of phosphoric acid tail gas production. Therefore, it is crucial to develop a catalyst and reaction system that can efficiently decompose sodium hypophosphite to release hydrogen.

[0003] In existing research, there are few reports on the efficient production of hydrogen by catalytic decomposition of sodium hypophosphite at room temperature. Most of its uses are as a phosphorus source to generate phosphides or as a reducing agent for organic matter. There is no catalyst and utilization system that can effectively catalyze its decomposition for hydrogen release. In many studies, metal phosphides have the advantages of excellent activity, easy regulation, corrosion resistance and low cost. They are widely used in hydrogen evolution reactions due to the charge transfer between metal and phosphorus and the characteristics of surface adsorption of active hydrogen atoms, such as decomposition of electrocatalytic hydrogen and catalytic production of hydrogen by aminoborane. In the synthesis technology of metal phosphides, high-temperature reduction of NaH2PO2 is mainly used to decompose PH3 to generate phosphides. The reaction process is high temperature and produces toxic gases. There is an urgent need for a new preparation technology that does not produce toxic gases while fully utilizing P and H in NaH2PO2.

[0004] Heterostructure catalysts have attracted much attention as efficient catalysts due to their synergistic effects and improved interfacial electron transfer capabilities. Constructing metal / metal phosphide (M / MP) heterostructure catalysts through green routes and applying them to hydrogen production reactions is undoubtedly an effective way to cleanly utilize P and H in NaH2PO2. At present, metal / metal phosphide heterostructures are mainly prepared by high-temperature calcination, accompanied by the release of toxic gases, which puts certain pressure on energy and the environment. In addition, the metal phosphide-based catalysts reported so far all decompose expensive aminoborane to release hydrogen, or electrocatalyze and photocatalyze hydrogen production under the action of electric current or light, lacking a cheap and simple system. Among the many energy utilization methods, solar energy as a clean energy is a very valuable energy source, and the system that produces excited state electron transfer through light dye sensitization is an effective means to efficiently utilize solar energy and optimize catalytic performance.

[0005] In summary, the innovative organic combination of dye-sensitized photocatalysis with the synthesis of metal / metal phosphide heterostructures and in situ decomposition of NaH2PO2 to produce hydrogen is expected to form a synthetic method and hydrogen production system with great application prospects. Summary of the invention

[0006] In view of the problems in the prior art of preparing metal / metal phosphide heterostructure catalysts, such as high energy consumption and generation of polluting gases, it is difficult to catalyze sodium hypophosphite to produce hydrogen, to achieve efficient utilization of sodium hypophosphite, and the need to catalyze sodium hypophosphite under conditions such as photocatalysis and electrocatalysis, the present invention provides a heterogeneous catalyst and a light-driven preparation method thereof, and the catalyst is used to decompose sodium hypophosphite to produce hydrogen to meet the needs of actual production applications. The catalyst does not require high-temperature calcination or heat treatment during preparation, and can be carried out under visible light drive. Moreover, when catalyzing the decomposition of sodium hypophosphite, no photocatalysis or electrocatalysis is required, and the catalytic decomposition can be performed by standing at room temperature.

[0007] The present invention first provides a method for preparing a heterogeneous structure catalyst M / MP, comprising the following steps:

[0008] Add a metal source, a phosphorus source and a photosensitizer to a mixed solvent in no particular order. After uniform mixing, stir under visible light to obtain an M / MP heterostructure catalyst dispersed in the solution. There are no special requirements for the conditions of the above preparation method, and it can be carried out at room temperature and pressure.

[0009] The mixed solvent is a mixed solvent of triethylamine (TEA) and deionized water; the heterogeneous structure catalyst M / MP is a nanosphere heterogeneous structure catalyst with grooves on the surface, and the M / MP heterogeneous structure catalyst obtained at this time is dispersed in the solution. The heterogeneous structure catalyst dispersed in the solution is post-treated to obtain nanoparticles of the heterogeneous structure catalyst; the phosphorus source is sodium hypophosphite monohydrate or sodium hypophosphite.

[0010] Preferably, the molar ratio of the metal source, phosphorus source and photosensitizer is (0.1-1.2): (10-100):

[0011] (0.05-2.4), the volume molar ratio of the mixed solvent to the metal source is (20-80) mL: (0.1-2) mmol; in the mixed solvent, triethylamine (TEA) accounts for 1.0-12% of the total mixed solvent by volume, and the rest is deionized water.

[0012] Preferably, the metal source is one of cobalt salt, nickel salt, iron salt and copper salt. The cobalt salt, nickel salt, iron salt and copper salt of the metal source can be various forms of metal salts, and there is no special requirement for the anion thereof, as long as it is water-soluble; more preferably, the metal source is one of cobalt nitrate, cobalt sulfate, cobalt chloride, nickel chloride, ferric chloride, cupric chloride, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, ferric chloride hexahydrate and cupric chloride dihydrate.

[0013] Preferably, the photosensitizer is eosin Y (water-soluble) or eosin Y (alcohol-soluble); the photosensitizer is a kind of organic dye, and the molecular formula of eosin Y (water-soluble) is C 20 H6Br4Na2O5, the molecular formula of the eosin Y (alcohol soluble) is or 20 H8Br4O5, since triethylamine is added to the raw material, eosin Y (alcohol soluble) is also suitable for the preparation of the heterogeneous catalyst in the present invention.

[0014] Preferably, the metal source, phosphorus source and photosensitizer are uniformly mixed in a mixed solvent, sealed, and stirred at 100-800 rpm for 1-96 hours under visible light illumination. The visible light source is a visible white light LED light source with a wavelength λ≥420nm and a power of 10-180W.

[0015] Preferably, hydrogen is collected in situ during the preparation process and can be detected by a gas chromatograph;

[0016] There is a hydrogen production reaction in the preparation process, and the reaction system has a good hydrogen production efficiency, with an average hydrogen production efficiency of 1.16-10.10 mL / h within 4 hours.

[0017] Among them, triethylamine in the mixed solvent can act as an electron donor, and a stable M / MP heterostructure catalyst can be generated in situ in a homogeneous aqueous solution system through a visible white light LED light source.

[0018] The mechanism of the above light-driven preparation process is:

[0019] Under light, eosin Y (EY) will reach an excited state to generate triplet EY * , E.Y. * It will first be reductively quenched by the presence of a large amount of triethylamine to form EY *- , E.Y. *- It has a strong enough reduction potential (E = -1.06 V vs. SCE) to reduce metal ions to generate zero-valent single metal nanoparticles; 2) the metal nanoparticles receive the excited state EY *- After the electrons are released, water is decomposed on the metal surface to generate active hydrogen [H]. At the same time, the zero-valent metal nanoparticles also catalyze H2PO2 - Generate atomic active hydrogen [H](H2PO2 - +H2O→HPO3 2- +H + +2[H]); 3) Atomic active hydrogen combines with each other to generate hydrogen (2[H]→H2↑), and on the other hand reacts with sodium hypophosphite in the solution to generate P(H2PO2 - +[H]→H2O+OH - +P), the reduced P phase combines with metal nanoparticles to form metal phosphide (MP); 4) After the metal element nanoparticles are generated by photoreduction, the metal element can serve as a catalytic phase substrate, further promoting the metal ions and hypophosphite to generate metal (M n+ +H2PO2 - +3OH - →M+HPO3 2- +2H2O), so the metal nanoparticles are preferentially generated in large quantities and continuously grow and aggregate in the system, and the P phase generated with the sodium hypophosphite on its surface can gradually combine with the metal to form MP, so within a certain period of time, an M / MP heterogeneous structure catalyst can be formed as a whole, and affected by the reaction process of nanoparticle growth, it presents a gully-like nanosphere structure formed by the hierarchical aggregation of small particles.

[0020] The M / MP heterogeneous structure catalyst prepared by the above method is dispersed in the solution. In order to obtain pure and dry nanoparticles of the M / MP heterogeneous structure catalyst, the following treatment is preferably performed:

[0021] 1) Add 10-60 mL of 75 wt% ethanol to 1-30 mL of the obtained M / MP heterostructure catalyst dispersed in the solution, perform ultrasonic cleaning for 1-30 min, centrifuge at 3000-10000 rpm for 5-20 min, and after the centrifugation, pour out the supernatant and take the solid at the bottom; the ultrasonic setting can be conventional, which will not be described here;

[0022] 2) Repeating the steps of adding ethanol, ultrasonic cleaning and centrifuging the bottom solid obtained in step 1) for 3-8 times;

[0023] 3) The solid obtained in step 2) is dried under vacuum at 60° C. for 1-6 h with a vacuum degree of 1-10 Pa to obtain pure and dry nanoparticles of the M / MP heterostructure catalyst.

[0024] The M / MP heterogeneous structure catalyst nanoparticles collected above are nanospheres formed by stacking layered nanosheets, with a grooved surface and a particle size of 50-200nm. The metal and phosphorus are evenly distributed, wherein the molar percentage of the metal is 49.7-98.2%, and the molar percentage of phosphorus is 1.8%-50.3%.

[0025] The present invention further provides an application of the M / MP heterogeneous structure catalyst in decomposing sodium hypophosphite to produce hydrogen. The M / MP heterogeneous structure catalyst directly decomposes sodium hypophosphite in water to produce hydrogen. The specific steps are: mixing the M / MP heterogeneous structure catalyst, sodium hypophosphite and water according to a mass feed ratio of (0.1-10): (100-1000): (0.1-10), sealing, and then detecting the generation of hydrogen by a gas chromatograph; the average hydrogen production rate over 4 hours is 33.95-60.83 mL·g cat -1 ·h -1 , has good hydrogen production performance and is a hydrogen storage system with good development prospects.

[0026] The reaction mechanism of the above hydrogen production process is:

[0027] 1) The M / MP heterostructure acts as a catalyst to catalyze the reaction of hypophosphite with water to generate phosphate, hydrogen ions and active hydrogen [H], and the reaction formula is:

[0028]

[0029] 2) Hypophosphite is reduced by active hydrogen [H] to generate phosphorus atoms (H2PO2 - +[H]→H2O+OH - +P), on the one hand, the highly active MP effectively catalyzes the active [H] to combine and efficiently generate H2, and promotes the decomposition of hypophosphite. The reaction formula is as follows:

[0030]

[0031] 3) On the other hand, the P phase generated with it further combines with the M phase in M / MP to form MP, which increases the proportion of metal phosphide MP in M / MP (M / MP+P→M / MP(MP%↑));

[0032] 4) This reciprocating catalysis forms a cyclic catalytic process, and eventually the MP catalyst is completely generated.

[0033] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0034] 1) The present invention synthesizes an M / MP heterostructure catalyst using a visible white light-driven dye-sensitized photocatalytic system at room temperature and pressure, synthesizes heterostructures of different proportions by adjusting the amount of added phosphorus source and the reaction time, and realizes in-situ catalytic decomposition of sodium hypophosphite to produce hydrogen.

[0035] 2) The M / MP catalyst directly catalyzes the new hydrogen storage material sodium hypophosphite to produce hydrogen; the heterogeneous structure synthesized by this method has a surface grooved nanosphere structure. Thanks to the special structure of the material, the electron transfer ability and active sites of the catalyst are increased, and the hypophosphite ions are effectively adsorbed to promote the production of hydrogen.

[0036] 3) The present invention overcomes the problems of high energy consumption and generation of pollutant gases in material preparation, and provides a new heterostructure preparation technology and a method for directly catalytically decomposing sodium hypophosphite. Its preparation does not require high-temperature calcination or heating, and the catalytic decomposition of sodium hypophosphite does not need to be carried out under photocatalytic or electrocatalytic conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a scanning electron microscope image of the Co / CoP heterostructure catalyst in Example 1 of the present invention;

[0038] Figure 2 is an element mapping distribution diagram of the Co / CoP heterostructure catalyst in Example 1 of the present invention;

[0039] Figure 3 is an X-ray diffraction pattern of the Co / CoP heterostructure catalyst in Example 1 of the present invention;

[0040] Figure 4 is the rate of hydrogen production from decomposition of sodium hypophosphite at different reaction times during the preparation of the Co / CoP heterostructure catalyst in Example 1 of the present invention;

[0041] Figure 5 is a scanning electron microscope image of the Ni / Ni heterostructure catalyst in Example 21 of the present invention;

[0042] Figure 6 is an element mapping distribution diagram of the Ni / NiP heterostructure catalyst in Example 21 of the present invention;

[0043] Figure 7 is an X-ray diffraction pattern of the Ni / NiP heterostructure catalyst in Example 21 of the present invention;

[0044] Figure 8 is the rate of hydrogen production from decomposition of sodium hypophosphite at different reaction times during the preparation of the Ni / NiP heterostructure catalyst in Example 21 of the present invention;

[0045] Fig. 9 is a scanning electron microscope image of the Fe / FeP heterostructure catalyst in Example 22 of the present invention;

[0046] Fig.10 is an element mapping distribution diagram of the Fe / FeP heterostructure catalyst in Example 22 of the present invention;

[0047] Fig.11 is an X-ray diffraction pattern of the Fe / FeP heterostructure catalyst in Example 22 of the present invention;

[0048] Fig.12 is the rate of hydrogen production from decomposition of sodium hypophosphite at different reaction times during the preparation of the Fe / FeP heterostructure catalyst in Example 22 of the present invention;

[0049] Fig.13 is a scanning electron microscope image of the Cu / Cu3P heterostructure catalyst in Example 23 of the present invention;

[0050] Fig.14 is an element mapping distribution diagram of the Cu / Cu3P heterostructure catalyst in Example 23 of the present invention;

[0051] Fig.15 is the X-ray diffraction pattern of the Cu / Cu3P heterostructure catalyst in Example 23 of the present invention;

[0052] Fig.16 is the rate of hydrogen production from decomposition of sodium hypophosphite at different reaction times during the preparation of the Cu / Cu3P heterostructure catalyst in Example 23 of the present invention;

[0053] Fig.17 is the rate of hydrogen production from decomposition of sodium hypophosphite at different reaction times during the preparation of the Co / CoP heterostructure catalyst in Example 24 of the present invention;

[0054] Fig.18 is the rate of hydrogen production from decomposition of sodium hypophosphite at different reaction times during the preparation of the Co / CoP heterostructure catalyst in Example 25 of the present invention;

[0055] Fig.19 It is the hydrogen production rate of decomposing sodium hypophosphite at different reaction times during the preparation process in Comparative Example 5 of the present invention;

[0056] Fig. 20 is the hydrogen production rate of direct decomposition of sodium hypophosphite by the Co / CoP heterostructure catalyst in Example 26 of the present invention;

[0057] Fig.21 is the hydrogen production rate of directly decomposing sodium hypophosphite by the Ni / NiP heterostructure catalyst in Example 27 of the present invention;

[0058] Fig. 22 is the hydrogen production rate of directly decomposing sodium hypophosphite by the Fe / FeP heterostructure catalyst in Example 28 of the present invention;

[0059] Fig.23 It is the hydrogen production rate of directly decomposing sodium hypophosphite by the Cu / Cu3P heterostructure catalyst in Example 29 of the present invention. DETAILED DESCRIPTION

[0060] In order to enable those skilled in the art to more clearly understand the technical solution, the technical solution of the present application is described in detail below in conjunction with specific embodiments and drawings. If the specific experimental conditions are not specified in the embodiments, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following embodiments, unless otherwise specified, can be obtained through commercial channels.

[0061] In some embodiments of the present invention, the method for preparing the M / MP heterostructure catalyst comprises:

[0062] At room temperature and pressure, a metal source, sodium hypophosphite monohydrate (NaH2PO2·H2O) and an organic dye eosin Y (water-soluble, C 20 H6Br4Na2O5) as a mixed metal source, a phosphorus source precursor and a photosensitizer; wherein the volume molar ratio of the mixed solvent to the metal salt is (20-80) mL: (0.1-2) mmol; in the above mixed solvent, the volume proportion of triethylamine (TEA) is 1.0%-12%, and the rest is deionized water.

[0063] The above substances are mixed evenly according to a proportion, sealed, placed under a visible white light LED light source for illumination and stirred for 1-96 hours to prepare a nanosphere M / MP heterostructure catalyst with a grooved surface. At this time, the M / MP heterostructure catalyst obtained is dispersed in a solution; the visible white light LED light source has a λ≥420nm and a power of 10W-180W.

[0064] In some embodiments of the present invention, cobalt chloride hexahydrate is used as a metal source to prepare a Co / CoP heterostructure catalyst dispersed in a solution according to the above method.

[0065] In some embodiments of the present invention, nickel chloride hexahydrate is used as a metal source to prepare a Ni / NiP heterostructure catalyst dispersed in a solution according to the above method.

[0066] In some embodiments of the present invention, ferric chloride hexahydrate is used as a metal source to prepare a Fe / FeP heterostructure catalyst dispersed in a solution according to the above method.

[0067] In some embodiments of the present invention, cupric chloride dihydrate is used as a metal source to prepare a Cu / Cu3P heterostructure catalyst dispersed in a solution according to the above method.

[0068] In order to obtain pure and dry M / MP heterostructure catalyst nanoparticles, the M / MP heterostructure catalyst dispersed in the solution obtained by the above method is subjected to the following treatments:

[0069] For every 1-30 mL of the M / MP heterogeneous structure catalyst dispersed in the solution, 10-60 mL of 75 wt% ethanol is added, poured into a centrifuge tube, ultrasonically cleaned for 1-30 minutes, and centrifuged at 3000-10000 rpm for 5-20 minutes. After the end, the supernatant is poured out to take the bottom solid, and the bottom solid is repeated for 3-8 times by adding ethanol, ultrasonic cleaning and centrifugation, and placed in a vacuum oven at 60°C for 1-6 hours with a vacuum degree of 1-10 Pa to obtain a pure M / MP heterogeneous structure catalyst. The ultrasound can be set in a conventional manner, which will not be repeated here.

[0070] The heterogeneous structure catalyst is composed of metal / metal phosphide, specifically Co / CoP, Ni / NiP, Fe / FeP, Cu / Cu3P heterogeneous structure catalyst nanospheres, with a grooved surface, a particle size of 50-200nm, and a uniform distribution of metal and phosphorus, wherein the molar percentage of metal is 49.7-98.2%, and the molar percentage of phosphorus is 1.8%-50.3%.

[0071] Some embodiments of the present invention also provide a method for efficiently decomposing sodium hypophosphite to produce hydrogen using an M / MP heterostructured catalyst. There are two ways to decompose sodium hypophosphite to produce hydrogen: the first is to collect hydrogen in situ during the preparation of the M / MP heterostructured catalyst; the second is to collect the prepared M / MP heterostructured catalyst and directly decompose sodium hypophosphite to produce hydrogen.

[0072] The first approach is to collect hydrogen in situ during the photocatalytic preparation of M / MP heterostructure catalysts. The average hydrogen production rate of the above approach over 4 h is 1.16-10.10 mL h-1 , with excellent hydrogen production performance.

[0073] The second approach is to use the collected M / MP heterostructure as a catalyst to directly decompose sodium hypophosphite to produce hydrogen. The specific steps are as follows:

[0074] The M / MP heterogeneous structure catalyst, sodium hypophosphite and water were mixed and added in a mass feed ratio of (0.1-10):(100-1000):(0.1-10), and the mixture was sealed. The generation of hydrogen could be detected immediately by a gas chromatograph. The reaction was continued for 4 hours, and the hydrogen production was recorded.

[0075] The above-mentioned route produces 33.95-60.83 mL·g of hydrogen in 4 h. cat -1 ·h -1 , and has good hydrogen production performance, and is a hydrogen storage system with development prospects.

[0076] The technical solution of the present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the scope of protection of the present invention. Example 1: Preparation of Co / CoP heterogeneous structure catalyst and in-situ decomposition of sodium hypophosphite to produce hydrogen

[0077] The Co / CoP heterostructure catalyst was prepared by the following method:

[0078] Pour 0.05mmol CoCl2·6H2O and 2.5mmol NaH2PO2·H2O into a test tube, add 0.05mmol eosin Y (water-soluble) and 29.1mL deionized water, shake well, add 0.9mL TEA (volume concentration of the total system is 3% v / v), seal, and then place under λ≥420nm, 90W LED light source, stir at 500rpm, and react for 4h. During this process, use an injection to sample the hydrogen generated in the test tube every 20 minutes, and detect it by gas chromatograph. After sampling, keep the inside of the test tube sealed and continue the reaction. After the reaction, centrifuge and collect to obtain Co / CoP.

[0079] After the reaction, let it stand for 30 minutes, pour out the supernatant, add 25mL75wt% ethanol, ultrasonically clean for 10 minutes, centrifuge at 5000rpm for 10 minutes, pour out the supernatant and take the bottom solid, repeat the above steps of adding ethanol, ultrasonic cleaning and centrifugation 5 times, put it in a vacuum oven with a vacuum degree of 5Pa, vacuum dry it at 60℃ for 1 hour, grind and collect to obtain the Co / CoP heterostructure catalyst.

[0080] from Figure 1It can be seen that the Co / CoP heterostructure is in the form of nano-spherical particles with a rough, grooved surface. The particle size is 50-200 nm as measured by the ruler in the picture.

[0081] from Figure 2 It can be seen that the Co / CoP heterostructure contains Co and P and is evenly distributed; as shown in Table 1, the molar ratio of the formed Co / CoP heterostructure catalyst is Co:P=1:0.199;

[0082] Table 1 Inductively coupled plasma emission spectrometer element ratios of Co / CoP, Ni / NiP, Fe / FeP and Cu / Cu3P heterostructure catalysts in Example 1, Example 21, Example 22 and Example 23

[0083]

[0084] Figure 3 The XRD of the Co / CoP heterostructure shows that Co / CoP shows characteristic peaks at 36.3° and 56.03°, representing the (111) and (020) crystal planes of the CoP phase (JCPDS No.29-0497), respectively. At the same time, it shows obvious characteristic peaks at 41.7°, 44.8°, 47.6° and 75.9°, representing the (100), (002), (101) and (110) crystal planes of the Co phase (JCPDS No.05-0727), respectively.

[0085] like Figure 4 As shown, by using a gas chromatograph to detect hydrogen, it can be seen that the Co / CoP heterostructure catalyst decomposes sodium hypophosphite in the preparation process to produce 40.17 mL of hydrogen in 4 hours, and the average hydrogen production rate is 10.04 mL / h.

[0086] Example 2: Preparation of Co / CoP heterostructure catalyst

[0087] Example 2 The amount of NaH2PO2·H2O in Example 1 was changed to 0.5 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0088] Example 3: Preparation of Co / CoP heterostructure catalyst

[0089] Example 3 The amount of NaH2PO2·H2O in Example 1 was changed to 1.0 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0090] Example 4: Preparation of Co / CoP heterostructure catalyst

[0091] Example 4 The amount of NaH2PO2·H2O in Example 1 was changed to 1.5 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0092] Example 5: Preparation of Co / CoP heterostructure catalyst

[0093] Example 5 The amount of NaH2PO2·H2O in Example 1 was changed to 2.0 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0094] Example 6: Preparation of Co / CoP heterostructure catalyst

[0095] Example 6 The amount of NaH2PO2·H2O in Example 1 was changed to 3.0 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0096] Example 7: Preparation of Co / CoP heterostructure catalyst

[0097] Example 7 The amount of NaH2PO2·H2O in Example 1 was changed to 3.5 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0098] Example 8: Preparation of Co / CoP heterostructure catalyst

[0099] Example 8 The amount of NaH2PO2·H2O in Example 1 was changed to 4.0 mmol, and the other substances were prepared in the same manner to prepare the Co / CoP heterostructure catalyst.

[0100] As shown in Table 2, the element content of the Co / CoP heterostructure catalysts prepared in Examples 2-8 was detected by inductively coupled plasma emission spectrometry. The results showed that for the catalysts formed under different amounts of NaH2PO2·H2O, the more molar amount of NaH2PO2·H2O, the greater the molar ratio of P to Co, and the greater the amount of CoP in the formed Co / CoP heterostructure.

[0101] Table 2 Inductively coupled plasma emission spectrometer element content test results and molar ratios of Co / CoP heterostructure catalysts prepared at different phosphorus source concentrations in Examples 2-8

[0102]

[0103] Example 9: Preparation of Co / CoP heterostructure catalyst

[0104] Example 9 The illumination reaction time in Example 1 was changed to 1 h, and the other materials were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0105] Example 10: Preparation of Co / CoP heterostructure catalyst

[0106] Example 10 The illumination reaction time in Example 1 was changed to 2 h, and the other materials were used to prepare the Co / CoP heterostructure catalyst in the same manner.

[0107] Example 11: Preparation of Co / CoP heterostructure catalyst

[0108] Example 11 The illumination reaction time in Example 1 was changed to 3 h, and the other substances were used to prepare the Co / CoP heterostructure catalyst in the same manner.

[0109] Example 12: Preparation of Co / CoP heterostructure catalyst

[0110] Example 12: The illumination reaction time in Example 1 was changed to 5 h, and the other substances were used to prepare the Co / CoP heterostructure catalyst in the same manner.

[0111] Example 13: Preparation of Co / CoP heterostructure catalyst

[0112] Example 13: The illumination reaction time in Example 1 was changed to 6 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0113] Example 14: Preparation of Co / CoP heterostructure catalyst

[0114] Example 14 The illumination reaction time in Example 1 was changed to 7 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0115] Example 15: Preparation of Co / CoP heterostructure catalyst

[0116] Example 15: The illumination reaction time in Example 1 was changed to 12 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0117] Example 16: Preparation of Co / CoP heterostructure catalyst

[0118] Example 16 The illumination reaction time in Example 1 was changed to 24 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0119] Example 17: Preparation of Co / CoP heterostructure catalyst

[0120] Example 17: The illumination reaction time in Example 1 was changed to 36 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0121] Example 18: Preparation of Co / CoP heterostructure catalyst

[0122] Example 18: The illumination reaction time in Example 1 was changed to 48 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0123] Example 19: Preparation of Co / CoP heterostructure catalyst

[0124] Example 19: The illumination reaction time in Example 1 was changed to 72 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0125] Example 20: Preparation of Co / CoP heterostructure catalyst

[0126] Example 20: The illumination reaction time in Example 1 was changed to 96 h, and the other substances were prepared using the same method to prepare the Co / CoP heterostructure catalyst.

[0127] As shown in Table 3, the proportion of P in the catalysts formed under different illumination times gradually increased, and a pure phase CoP catalyst was gradually formed, which explained the dynamic change process in the light-driven synthesis of heterostructures.

[0128] Table 3 Inductively coupled plasma emission spectrometer element content test results and molar ratios of Co / CoP heterostructure catalysts under different illumination times in Examples 9-20

[0129] Example 21: Preparation of Ni / NiP heterostructure catalyst and in-situ decomposition of sodium hypophosphite to produce hydrogen

[0130] The Ni / NiP heterostructure catalyst was prepared by the following method.

[0131] Pour 0.05mmol NiCl2·6H2O and 2.0mmol NaH2PO2·H2O into a test tube, add 0.06mmol eosin Y (water-soluble) and 28.5mL deionized water, shake well, add 1.5mL TEA (volume concentration of the total system is 5% v / v), seal, and then place under λ≥420nm, 60W LED light source, stir at 500rpm, and react for 6h. During this process, use an injection to sample the hydrogen generated in the test tube every 20 minutes, and detect it by gas chromatograph. After sampling, keep the inside of the test tube sealed and continue the reaction. After the reaction, centrifuge and collect to obtain Ni / NiP.

[0132] After the reaction, let it stand for 30 minutes, pour out the supernatant, add 30mL 75wt% ethanol, ultrasonically clean for 10 minutes, centrifuge at 3000rpm for 10 minutes, pour out the supernatant and take the bottom solid, repeat the above steps of adding ethanol, ultrasonic cleaning and centrifugation for 3 times, put it in a vacuum oven with a vacuum degree of 5Pa, vacuum dry it at 60℃ for 1 hour, grind and collect to obtain Ni / NiP heterostructure catalyst.

[0133] from Figure 5 It can be seen that the Ni / NiP heterostructure catalyst is composed of many nanoparticles stacked together to form a fine groove-shaped nanosphere structure. The particle size measured by the ruler in the picture is 50-200nm.

[0134] from Figure 6 It can be seen that the Ni / NiP heterostructure contains Ni and P and is evenly distributed; as shown in Table 1, the molar ratio of the formed Ni / NiP heterostructure catalyst is Ni:P=1:0.951.

[0135] like Figure 7 As shown in Figure 1, the XRD of the Ni / NiP heterostructure shows that Ni / NiP shows a characteristic peak at 34.9°, representing the (210) crystal plane of the NiP phase (JCPDS No.18-0882). At the same time, it shows obvious characteristic peaks at 44.5° and 58.4°, representing the (011) and (012) crystal planes of the Ni phase (JCPDS No.45-1027), respectively.

[0136] like Figure 8 As shown, by using a gas chromatograph to detect hydrogen, it can be seen that the Ni / NiP heterostructure catalyst decomposes sodium hypophosphite in the preparation process to produce 40.40 mL of hydrogen in 4 hours, and the average hydrogen production rate is 10.10 mL / h.

[0137] Example 22: Preparation of Fe / FeP heterostructure catalyst and in-situ decomposition of sodium hypophosphite to produce hydrogen

[0138] The Fe / FeP heterostructure catalyst was prepared by the following method.

[0139] Pour 0.05mmol FeCl3·6H2O and 3.0mmol NaH2PO2·H2O into a test tube, add 0.05mmol eosin Y (water-soluble) and 29.1mL deionized water, shake well, add 0.9mL TEA (volume concentration of the total system is 3% v / v), seal, and then place under λ≥420nm, 60W LED light source, stir at 500rpm, and react for 6h. During this process, use an injection to sample the hydrogen generated in the test tube every 20 minutes, and detect it by gas chromatograph. After sampling, keep the inside of the test tube sealed and continue the reaction. After the reaction, collect by centrifugation to obtain Fe / FeP.

[0140] After the reaction, let it stand for 30 minutes, pour out the supernatant, add 50mL 75wt% ethanol, ultrasonically clean for 10 minutes, centrifuge at 3000rpm for 7 minutes, pour out the supernatant and take the bottom solid, repeat the above steps of adding ethanol, ultrasonic cleaning and centrifugation for 3 times, put it in a vacuum oven with a vacuum degree of 5Pa, vacuum dry it at 60℃ for 1 hour, grind and collect to obtain Fe / FeP heterostructure catalyst.

[0141] from Fig. 9 It can be seen that the Fe / FeP heterostructure is also composed of many nanoparticles stacked together to form a fine groove-shaped nanosphere structure. The particle size measured by the ruler in the picture is 50-200nm.

[0142] from Fig.10 It can be seen that the Fe / FeP heterostructure contains Fe and P and is evenly distributed; as shown in Table 1, the molar ratio of the formed Fe / FeP heterostructure catalyst is Fe:P=1:0.061.

[0143] like Fig.11 As shown in Figure 1, the XRD of the Fe / FeP heterostructure shows that Fe / FeP shows characteristic peaks at 35.5° and 56.1°, representing the (120) and (031) crystal planes of the FeP phase (JCPDS No.39-0809). At the same time, it shows a characteristic peak at 43.0°, representing the (100) crystal plane of the Fe phase (JCPDS No.50-1275).

[0144] like Fig.12 As shown, by using a gas chromatograph to detect hydrogen, it can be seen that the Fe / FeP heterostructure catalyst decomposes sodium hypophosphite in the preparation process to produce 4.61 mL of hydrogen in 4 hours, and the average hydrogen production rate is 1.16 mL / h.

[0145] Example 23: Preparation of Cu / Cu3P heterostructure catalyst and in-situ decomposition of sodium hypophosphite to produce hydrogen

[0146] The Cu / Cu3P heterostructure catalyst was prepared by the following method.

[0147] Pour 0.05mmol CuCl2·2H2O and 2.5mmol NaH2PO2·H2O into a test tube, add 0.05mmol Eosin Y (water-soluble) and 28.5mL deionized water, shake well, add 1.5mL TEA (volume concentration of the total system is 5% v / v), seal, and then place under λ≥420nm, 30W LED light source, stir at 500rpm, and react for 6h. During this process, use an injection to sample the hydrogen generated in the test tube every 20 minutes, and detect it through a gas chromatograph. After sampling, keep the inside of the test tube sealed and continue the reaction. After the reaction, centrifuge and collect to obtain Cu / Cu3P.

[0148] After the reaction, let it stand for 30 minutes, pour out the supernatant, add 50mL75wt% ethanol, ultrasonically clean for 10 minutes, centrifuge at 3000rpm for 10 minutes, pour out the supernatant and take the bottom solid, repeat the above steps of adding ethanol, ultrasonic cleaning and centrifugation 5 times, put it in a vacuum oven with a vacuum degree of 5Pa, vacuum dry it at 60℃ for 1 hour, grind and collect to obtain the Cu / Cu3P heterostructure catalyst.

[0149] from Fig.13 It can be seen that the Cu / Cu3P heterostructure presents a structure of finer nanoparticles stacked together to form a fine groove-shaped nanosphere. The particle size is measured by the ruler in the picture and is between 50-200nm.

[0150] from Fig.14 It can be seen that the Cu / Cu3P heterostructure contains Cu and P and is evenly distributed; as shown in Table 1, the molar ratio of the formed Cu / Cu3P heterostructure catalyst is Cu:P=1:0.019.

[0151] like Fig.15 As shown in Figure 1, the XRD of the Cu / Cu3P heterostructure shows that Cu / Cu3P shows a characteristic peak at 36.2°, representing the (112) crystal plane of the Cu3P phase (JCPDS No.02-1263). At the same time, characteristic peaks at 43.3°, 50.4° and 74.1° are shown, representing the (111), (200) and (220) crystal planes of the Cu phase (JCPDS No.04-0836), respectively.

[0152] like Fig.16As shown, by using a gas chromatograph to detect hydrogen, it can be seen that the Cu / Cu3P heterostructure catalyst decomposes sodium hypophosphite for 4 hours to produce 16.57 mL of hydrogen during the preparation process, and the average hydrogen production rate is 4.14 mL / h.

[0153] Example 24: Preparation of Co / CoP heterostructure catalyst and in-situ decomposition of sodium hypophosphite to produce hydrogen

[0154] Example 24: Replace CoCl2·6H2O in Example 1 with Co(NO3)2·6H2O, and prepare the Co / CoP heterostructure catalyst using the same method as Example 1 for other substances.

[0155] like Fig.17 As shown, by using a gas chromatograph to detect hydrogen, it can be seen that the Co / CoP heterostructure catalyst decomposes sodium hypophosphite for 4 hours to produce 40.94 mL of hydrogen during the preparation process, and the average hydrogen production rate is 10.24 mL / h.

[0156] Example 25: Preparation of Co / CoP heterostructure catalyst and in-situ decomposition of sodium hypophosphite to produce hydrogen

[0157] Example 25: The CoCl2·6H2O in Example 1 is replaced by CoSO4·7H2O, and the other substances are prepared by the same method as Example 1 to prepare a Co / CoP heterostructure catalyst.

[0158] like Fig.18 As shown, by using a gas chromatograph to detect hydrogen, it can be seen that the Co / CoP heterostructure catalyst decomposes sodium hypophosphite for 4 hours to produce 40.41 mL of hydrogen during the preparation process, and the average hydrogen production rate is 10.10 mL / h.

[0159] Examples 24 and 25 illustrate that cobalt salts with different anions have no effect on the generation of hydrogen.

[0160] Comparative Example 1: Component-deficient experiment

[0161] Comparative Example 1: A heterogeneous structure catalyst was prepared by a method substantially the same as that in Example 1, except that no light irradiation was performed. Other aspects were the same as those in Example 1.

[0162] Comparative Example 2: Component-deficient experiment

[0163] Comparative Example 2 uses a method substantially the same as that in Example 1 to prepare a heterogeneous structure catalyst, except that eosin Y (water-soluble) is not added, and the rest is the same as Example 1.

[0164] Comparative Example 3: Component-deficient experiment

[0165] Comparative Example 3: A heterogeneous structure catalyst was prepared by using a method substantially the same as that in Example 1, except that CoCl2·6H2O was not added. The other conditions were the same as those in Example 1.

[0166] Comparative Example 4: Component-deficient experiment

[0167] Comparative Example 4 uses a method substantially the same as that in Example 1 to prepare a heterogeneous structure catalyst, except that TEA is not added, and the rest is the same as Example 1.

[0168] As shown in Table 4, during the material preparation process of Comparative Examples 1-4, the hydrogen generated during the preparation process was collected and detected according to the same method as in Example 1, and it was found that the generation of hydrogen could not be detected by gas chromatograph, indicating that light, eosin Y (water-soluble), metal source and TEA are necessary conditions for the reaction.

[0169] Table 4 4h hydrogen production of comparative examples 1-4

[0170]

[0171] Comparative Example 5: Component-deficient experiment

[0172] Comparative Example 5: A heterogeneous structure catalyst was prepared by a method substantially the same as that in Example 1, except that NaH2PO2·H2O was not added. The other conditions were the same as those in Example 1.

[0173] like Fig.19 As shown, when no phosphorus source was added to Comparative Example 5, the generation of 1.6 ml of hydrogen in 4 hours was detected by gas chromatograph during the material preparation process, and the hydrogen production rate was much lower than that of Example 1, indicating that the generation of hydrogen was mainly through the decomposition of sodium hypophosphite.

[0174] The following Examples 26-29 are application examples of the above catalyst.

[0175] Example 26: Decomposition of sodium hypophosphite to produce hydrogen using Co / CoP heterostructure catalyst

[0176] Weigh 5 mg of the Co / CoP heterostructure catalyst prepared in Example 1, pour it into a test tube, add 2.5 mmol NaH2PO2·H2O and 30 mL of deionized water, shake well, seal, react for 4 h, and measure the hydrogen production using a gas chromatograph.

[0177] like Fig. 20 As shown in Figure 2, the average hydrogen production rate of the Co / CoP heterostructure catalyst in water was 60.83 mL·g for 4 h. cat -1 ·h -1 .

[0178] Example 27: Ni / NiP heterostructure catalyst catalyzes the decomposition of sodium hypophosphite to produce hydrogen

[0179] Weigh 5 mg of the Ni / NiP heterostructure catalyst prepared in Example 21, pour it into a test tube, add 2.5 mmol NaH2PO2·H2O and 30 mL of deionized water, shake well, seal, react for 4 h, and measure the hydrogen production using a gas chromatograph.

[0180] like Fig.21 As shown in Figure 2, the average hydrogen production rate of the Ni / NiP heterostructure catalyst in water was 50.13 mL·g for 4 h. cat -1 ·h -1 .

[0181] Example 28: Fe / FeP heterostructure catalyst catalyzes the decomposition of sodium hypophosphite to produce hydrogen

[0182] Weigh 5 mg of the Fe / FeP heterostructure catalyst prepared in Example 22, pour it into a test tube, add 2.5 mmol NaH2PO2·H2O and 30 mL of deionized water, shake well, seal, react for 4 h, and measure the hydrogen production using a gas chromatograph.

[0183] like Fig. 22 As shown in Figure 2, the average hydrogen production rate of the Fe / FeP heterostructure catalyst in water was 33.95 mL·g for 4 h. cat -1 ·h -1 .

[0184] Example 29: Decomposition of sodium hypophosphite to produce hydrogen using Cu / Cu3P heterostructure catalyst

[0185] Weigh 5 mg of the Cu / Cu3P heterostructure catalyst prepared in Example 23, pour it into a test tube, add 2.5 mmol NaH2PO2·H2O and 30 mL of deionized water, shake well, seal, react for 4 h, and measure the hydrogen production using a gas chromatograph.

[0186] like Fig.23 As shown in Figure 2, the average hydrogen production rate of Cu / Cu3P heterostructure catalyst in water was 43.58 mL·g for 4 h. cat -1 ·h -1 .

[0187] In summary, the present invention synthesizes an M / MP heterostructure catalyst using a visible white light-driven dye-sensitized system at room temperature and pressure, and realizes the catalytic decomposition of sodium hypophosphite to produce hydrogen. When the catalyst is used to catalyze the decomposition of sodium hypophosphite, it does not need to be carried out under photocatalysis or electrocatalysis, and hydrogen can be produced by placing it at room temperature. The present invention overcomes the problems of high energy consumption and generation of pollutant gases in material preparation, and provides a new heterostructure preparation technology and a method for catalytic decomposition of sodium hypophosphite.

[0188] The above embodiments are one or more specific implementation methods selected by the present invention. Common changes and substitutions made by those skilled in the art within the scope of this technical solution should be included in the protection scope of the present invention.

Claims

1. A method for preparing a heterogeneous structure catalyst, characterized in that: The following steps are involved: Adding a metal source, a phosphorus source and a photosensitizer to a mixed solvent, mixing them evenly, and stirring them under visible light to obtain a heterogeneous structure catalyst dispersed in the solution, wherein the heterogeneous structure catalyst dispersed in the solution is post-treated to obtain nanoparticles of the heterogeneous structure catalyst; The mixed solvent is a mixed solvent of triethylamine and deionized water; The phosphorus source is sodium hypophosphite monohydrate or sodium hypophosphite.

2. The method for preparing a heterogeneous structure catalyst according to claim 1, characterized in that: The molar ratio of the metal source, the phosphorus source and the photosensitizer is (0.1-1.2):(10-100):(0.05-2.4), and the volume molar ratio of the mixed solvent to the metal source is (20-80) mL:(0.1-2) mmol; in the mixed solvent, the volume proportion of triethylamine in the total mixed solvent is 1.0-12%, and the rest is deionized water.

3. The method for preparing a heterogeneous structure catalyst according to claim 1, characterized in that: The metal source is one of cobalt salt, nickel salt, iron salt and copper salt, and the photosensitizer is water-soluble eosin Y or alcohol-soluble eosin Y.

4. The method for preparing a heterogeneous structure catalyst according to claim 3, characterized in that: The metal source is one of cobalt nitrate, cobalt sulfate, cobalt chloride, nickel chloride, ferric chloride, cupric chloride, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, ferric chloride hexahydrate, and cupric chloride dihydrate.

5. The method for preparing a heterogeneous structure catalyst according to claim 1, characterized in that: After the metal source, phosphorus source and photosensitizer are uniformly mixed in a mixed solvent, the mixture is stirred at 100-800 rpm for 1-96 hours under visible light illumination. The visible light source is a visible white light LED light source with a wavelength λ≥420nm and a power of 10-180W.

6. The method for preparing a heterogeneous structure catalyst according to claim 1, characterized in that: Hydrogen was collected in situ during the preparation process.

7. The method for preparing a heterogeneous structure catalyst according to claim 1, characterized in that: The heterogeneous structure catalyst dispersed in the solution is post-treated to obtain pure and dry nanoparticles of the heterogeneous structure catalyst, and the specific method is as follows: 1) Add 10-60 mL of 75 wt% ethanol to 1-30 mL of the heterogeneous structure catalyst dispersed in the solution, ultrasonically clean for 1-30 min, centrifuge at 3000-10000 rpm for 5-20 min, and after the centrifugation, pour out the supernatant and take the solid at the bottom; 2) Repeating the steps of adding ethanol, ultrasonic cleaning and centrifuging the bottom solid obtained in step 1) for 3-8 times; 3) The solid obtained in step 2) is dried under vacuum at 60° C. for 1-6 h with a vacuum degree of 1-10 Pa to obtain pure and dry nanoparticles of the M / MP heterostructure catalyst.

8. Nanoparticles of heterogeneous structure catalyst prepared by the preparation method according to claim 1, characterized in that: The nanoparticles of the heterogeneous structure catalyst are nanospheres with grooves on the surface, with a particle size of 50-200nm, a metal molar percentage of 49.7-98.2%, and a phosphorus molar percentage of 1.8%-50.3%.

9. Application of the heterogeneous structure catalyst nanoparticles according to claim 8 in decomposing sodium hypophosphite to produce hydrogen, characterized in that: The heterogeneous structure catalyst directly decomposes sodium hypophosphite in water to generate hydrogen.

10. The use according to claim 9, characterized in that: The heterogeneous structure catalyst, sodium hypophosphite and water are mixed according to the mass feed ratio of (0.1-10):(100-1000):(0.1-10) to generate hydrogen.